2013
DOI: 10.1111/jmcb.12041
|View full text |Cite
|
Sign up to set email alerts
|

Declining Effects of Oil Price Shocks

Abstract: In recent years, output responses to oil price shocks have not only been weaker, but have also reached their trough earlier. This paper builds a model that incorporates a realistic structure of U.S. petroleum consumption and explores three possible explanations for the changes. The possible factors considered are (i) deregulation in the transportation industry, (ii) improved energy efficiency, and (iii) a lower degree of persistence of oil price shocks. Under realistic parameter values, the three factors play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 78 publications
2
8
0
1
Order By: Relevance
“…From the foregoing, it can be suggested that Nigerian economic growth and construction growth are independent of oil price fluctuation. This result, therefore, aligned itself with [19,36,[51][52][53][54][55] who argue that the effects are less disruptive as a result of oil becoming less relevant in the economic equation of many countries in the recent time. It also agreed with [41,[56][57][58][59] who found that the effect is asymmetric and there is no clear effect of oil price changes on the economic growth.…”
Section: Granger Causality Testsupporting
confidence: 74%
See 1 more Smart Citation
“…From the foregoing, it can be suggested that Nigerian economic growth and construction growth are independent of oil price fluctuation. This result, therefore, aligned itself with [19,36,[51][52][53][54][55] who argue that the effects are less disruptive as a result of oil becoming less relevant in the economic equation of many countries in the recent time. It also agreed with [41,[56][57][58][59] who found that the effect is asymmetric and there is no clear effect of oil price changes on the economic growth.…”
Section: Granger Causality Testsupporting
confidence: 74%
“…While some claim that oil price fluctuation exerts adverse impact on macroeconomic variables [1,[7][8][9][10][11]; others found that crude oil price fluctuation exert positive influence on the economic growth [16,37,48,50]. Still, some others argue that the effects are less disruptive and also not as significant as thought since oil is becoming less relevant in the economic equation of many countries in the recent time [19,36,[51][52][53][54][55], while others found that the effect is asymmetric and there is no clear effect of oil price changes on the economic growth [41,[56][57][58][59] since the impact of oil price fluctuations is considered to be different for oil importing and exporting countries [48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, while Hamilton (2003) quantifies the different effects on economic activities between oil price increases and decreases, Baumeister and Peersman (2013) document the time-varying effects of oil supply shocks on the economy. Other studies include Huang et al (2005), Rahman and Serletis (2011), Hamilton (2011), Katayama (2013, Baumeister and Kilian (2016b), and Cross and Nguyen (2017). Therefore, it is also crucial to consider possible nonlinear relationships between the energy prices and real economy.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of empirical and theoretical literature that analyze the impacts of the oil shocks of 1970s claim that oil price shocks exert adverse impacts on different macroeconomic indicators by raising production and operational costs (Hamilton (1983), Burbridge & Harrison (1984), Gisser & Goodwin (1986), Mork (1989), Jones & Kaul (1996), Shiu-Sheng Chen & Chen (2007), etc.). However, recent studies argue that the effects of oil price shocks on macroeconomic variables such as inflation are not as large and significant as they were in the 1970s because producers have continuously substituted away from oil over time (e.g., Hooker, 2002;Bachmeier and Cha, 2011;Katayama, 2013).…”
Section: Macroeconomic Implications Of Oil Price Volatilitymentioning
confidence: 99%